RECHTVINDING WASIAT WAJIBAH AHLI WARIS BEDA AGAMA PERSPEKTIF POST-POSITIVISME - Dafizki, Ashlih; Hanani, Silfia; Rozi, Syafwan (Universitas Nurul Jadid, 2024)
ABSTRACTThe obligatory bequest given to heirs of different religions represents a form of legal innovation established by the Supreme Court. However, this decision is contradictory within Islamic law. According to post-positivism theory, granting an obligatory bequest to heirs of different religions is a form of legal innovation carried out by judges related to Islamic family law, thereby aligning with the evolution of the times. This article aims to explore rechtvinding (legal discovery) regarding the obligatory bequest to heirs of different religions from a post-positivism perspective. The research method employed is library research, utilizing a post-positivism perspective. Primary sources include Supreme Court decision directories, while secondary sources consist of books, articles, and various online writings related to the discussion. The rechtvinding conducted by the Supreme Court is analyzed using post-positivism theory. Consequently, the findings of this research indicate that the Supreme Court's granting of an obligatory bequest to heirs of different religions is due to several reasons. These include historical factors, the use of sociological interpretation methods in legal determination, employing argumentum per analogiam in legal innovation, the existence of Islamic inheritance law among other inheritance laws, the choice of religion as part of human rights, and legal theory recognizing legal principles and deviations from those principles.Keywords: Legal Innovation, Obligatory Bequests, Different Religions, Post-Positivism